Reinterpretasi Pertunjukan Tradisional Rapai Bubee: Pewarisan Kesenian Tradisional Kabupaten Pidie Jaya ke dalam Dokumentasi Audio Digital - Tria Ocktarizka; Rizki Mona Dwi Putra (Universitas Negeri Medan, 2025)
Rapa'i Bubee is a traditional art form that originated and developed in the Meureudu area of ​​Pidie Jaya. Rapai Bubee, a ritualistic art form featuring musical and movement attractions, has been recognized as an Intangible Cultural Heritage of Humanity. However, its existence has faded, necessitating innovation in the form of digital audio documentation research and art and cultural preservation. Generally, research on the Rapa'i Bubee art form is limited to movement; musical research is rare. This study offers an innovative approach to Rapa'i Bubee music, exploring the local wisdom of the Pidie Jaya Regency community by digitally documenting Rapa'i Bubee in the modern era. This research uses the Artistic Research Method with a reinterpretation approach. This research provides a reinterpretation of the form of the rapai bubee performance in the form of taboh tapoh musical expression through the creative process of digital audio recording. This research has three stages, namely: a. Formulation of Rapa'i Bubee Musical Syair and Rhythm of Rapa'i Bubee Beats, b. determining the design of the Record/Record, c. development of musical innovation by utilizing digital audio technology. In this research, the researcher focuses on the musical aspects of the Rapai Bubee art, which includes the playing of rapa'i instruments and the sung poetry. Researchers are leveraging the latest technological advances in cultural preservation efforts, specifically through digital audio recording. Taboh tapoh is a term derived from the Acehnese language, where taboh means percussion and tapoh means blow. Taboh tapoh represents the Rapai Bubee performance, featuring a variety of rapai beats, ranging in speed from slow to fast.